Analisis Ketidakseimbangan Pembebanan Arus Netral Dan Losses Di Jaringan Distribusi - Khoerudin Khoerudin; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The electricity system in the office complex of the Rokan Hulu Regent District has a problem of load imbalance. One of the causes is the unequal loading factor at each line of its phase, or becauseof the unequal load switching time. As a result of the imbalance of loading resulted in the electric current in the neutral conductor. The current flowing in the neutral conductor causes losses. Thisresearch discusses the load imbalance in PP 129 distribution transformer that supply 6 buildings, namely the Rokan Hulu UPT Provincial Revenue Service, the Financial and Asset ManagementAgency, the Regional Revenue Agency, the Youth and Sports Education Agency, the Office Health and Food Crops and Horticulture Service. The method used is current and voltage measurement onthe transformer and also on the panels in each building using Digital Clamp Meter and Hexing HXE320. Load imbalance analysis from measuring data will be compared with IEEEstd 466-1980 analysis from measured data shows large load imbalances occured (26.4%) with neutral current 22.1 A and exceeds the 20% threshold from IEEE std.466-1980. This load imbalance caused 481 Watt losses due to current flow in the neutral conductor. Installation of JTR connection points thatare not adjusted with connection scheme is the cause of load imbalance.Keywords: load imbalance, neutral current, power losses.